(untitled) (Bangladesh Journal of Medical Science, 2025)
Objective This research aimed to reveal the environmental risk factors for dengue hemorrhagic fever (DHF) in the mountainous areas of Yogyakarta Province, Indonesia. Materials and methods Two mountainous areas were chosen: Gunungkidul (GK), a relatively dry mountainous area, and Kulon Progo (KP), a wet mountainous area. The area of settlement and shoreline distance were determined using Geographic Information System (GIS). Rainfall data and rainy days were obtained from the Local Climatology Agency. Data for DHF were obtained from the Regency Health Office. The correlation between DHF cases and independent variables was analyzed using the Spearman rank test. Results From 2015 to 2019, 2,796 cases of DHF occurred in GK, and 775 cases in KP. The highest incidences were in the two capital cities. DHF cases correlated with residential area in GK (p = 0.000, r 0.615) and KP (p = 0.000; r 0.426), altitude in GK (p = 0.000, r -0.321) and KP (p = 0.046, r 0.312), rainfall in GK (p = 0.000, r 0.505) and KP (p = 0.016, r -0.309), and rainy days in GK (p = 0.002, r 0.394) and KP (p = 0,032, r -0.277). DHF cases did not correlate with shoreline distance in either region (GK p = 0.911; KP p = 0.068). Conclusion The DHF risk factors in dry and wet mountainous areas were similar, but some had different directions. Settlement area was positively correlated with DHF. Rainfall and rainy days were positively correlated with DHF in dry mountainous areas but negatively correlated in wet mountainous areas. Altitude was positively correlated with DHF in wet but negatively correlated in dry mountainous areas. The incidence of DHF in mountainous areas was not affected by shoreline distance. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 246-255